Preliminary Psychometric Properties of the Gratitude Questionnaire in Peruvian College Students: A Comparison of the GQ-6 and GQ-5 - Franco-Jimenez, Andrei (2026)
Introduction: Gratitude is associated with psychological well-being and reduced psychopathology; however, the widely used Gratitude Questionnaire-6 (GQ-6) has shown inconsistent psychometric performance across cultures, particularly due to Item 6. In Latin America, evidence suggests that the abbreviated GQ-5 performs better, but no validation study has been conducted in the Peruvian context. Objective: This study examined the psychometric properties of the Gratitude Questionnaire-6 (GQ-6) and its revised version, the Gratitude Questionnaire-5 (GQ-5), in a sample of 444 Peruvian college students. Method: Participants completed the Spanish version of the Gratitude Questionnaire adapted by Quezada Berumen et al. (2023), along with additional measures to assess convergent validity. We conducted Exploratory Graph Analysis (EGA) and confirmatory factor analysis (CFA) to evaluate the dimensional structure and model fit. We also assessed measurement invariance by sex and internal consistency. Results: The GQ-6 demonstrated poor fit indices; therefore, we removed Item 6, and the remaining items constituted the GQ-5. The initial GQ-5 model still required modifications; correlating the error terms between Items 4 and 5 yielded a good fit (χ²(4) = 8.762, CFI = 0.998, RMSEA = 0.052, TLI = 0.995, SRMR = 0.018). The final GQ-5 model demonstrated acceptable internal consistency (ω = 0.73) and measurement invariance across sex. It also showed good convergent validity, correlating positively with self-efficacy (r = 0.31), mindfulness (r = 0.34), and well-being (r = 0.20), and negatively with depression (r = –0.26). Conclusion: This adaptation underscores the importance of cultural adjustments and supports the GQ-5 as a reliable tool for assessing gratitude among Peruvian students in research and clinical contexts.